An effective way to solve the abnormal oxidation behavior of Fe in Ti(C, N)-304ss cermet. (15th July 2019) - He, Lin; Gao, Yimin; Li, Yefei; Liu, Zhiwei; Zhai, Wenyan; Yuan, Wei; Chen, Wenqing; Yan, Wentao
Highlights: The oxidation behavior of the TiB2 /Ti(C, N)-304ss cermet during early oxidation stage was investigated. The abnormal oxidation behavior of Fe in this cermet was relieved with the addition of WC and TiB2 . The mechanism of relieving the abnormal oxidation behavior was revealed. Abstract: WC and TiB2 were added into Ti(C, N)-304ss cermet to relieve an abnormal oxidation behavior of Fe in this cermet. During high-temperature oxidation (650 °C), the volume swelling of WO3 eliminated the gap led by the volume shrinkage of TiO2 . Liquid B2 O3 covered the oxidation surface or filled in cracks, forming a dense oxidation layer. As a result, the abnormal oxidation behavior was relieved. The oxidation mechanism was investigated using FESEM, XRD, LSCM, and AFM. Fe atoms outward diffused to the surface along with the TiO2 /304ss boundary forming ring-structure oxide and across the TiO2 generating aggregated oxide on TiO2 surface.